(untitled) (Journal of the College of Basic Education, 2022)
It is an accepted fact that the goal of teaching is to achieve the desirable behavior of the learner And his tool in that is various factors and variables, on top of which stands the teacher and his strategy in achieving change In that behavior through great effort to increase the learner’s mental ability to store information And retrieve and benefit from it whenever needed